GOVERNANCE AND ETHICS IN PUBLIC ADMINISTRATION WITH A FOCUS ON ETHICAL PRINCIPLES AND DECISION-MAKING PROCESSES - G. Mohan; Kumar, Yogendra (International Journal of Research -GRANTHAALAYAH, 2024)
Good governance is the foundation of good public administration, as it makes administration accountable, transparent, and honest in their decision-making. This study has discussed the ethics compliance of the public administrators and has discussed their effects on the effectiveness of decision making and governance. The compliance with five major ethical principles, including Integrity, Transparency, Accountability, Fairness, and Responsiveness, and the associations with the performance and governance indicators of the low level of corruption, high level of public trust, and policy implementation were assessed using data of 100 administrators. The findings suggest that increased ethical compliance is related positively to better decision-making and better governance results. These results highlight the essence of the introduction of ethical frameworks in the administrative practice to enhance the institutional performance and trust in the administration.